Vanadium complexes of hydroxamic acids: Synthesis, characterisation and cytotoxicity investigation / Amalina Mohd Tajuddin - Amalina, Mohd Tajuddin (Faculty of Applied Sciences, 2009)
Two hydroxamic acid ligands, benzohydroxamic acid (BHA) and salicylhydroxamic acid (SHA) which are commercially available are reacted with vanadyl sulphate to obtain new hydroxamic acid complexes, [VO(BHA)2(H2O)] and [VO(SHA)2(H2O)]. The ratio of benzohydroxamic acid and salicylhydroxamic acid with vanadyl sulphate is 2:1 (BHA:VOSO4 and SHA:VOSO4). The hydroxamic acid ligands and complexes are characterised by various techniques which are elemental analysis, IR spectroscopy, 1H NMR, magnetic susceptibility measurements and melting point determination. The results suggest that the hydroxamic acid ligands coordinate to the metal ion as singly deprotonated hydroxamato via the oxygen of the carbonyl group and hydroxyl group in bidentate manner and one molecule of water. The cytotoxicity of the ligands and their vanadyl complexes are evaluated in-vitro using Chang liver cell culture. The ligands and [VO(SHA)2(H2O)] are found to be non-toxic whereas [VO(BHA)2(H2O)] is very mildly toxic with the lowest cell viability of 54.9% at 100 μM after 72 h of exposure